Spaces of geographical thought deconstructing human geography's binaries - Cloke, Paul 1953-; Johnston, Ron 1941-2020 (SAGE, 2005)
Examining key ideas - like space and place - which inform the geographic imagination, this text discusses the core conceptual vocabulary of human geography
Neue Seitenzählung in jedem Kapitel, abweichend von Seitenzählung in print-Version
Keywords: Human geography -- Philosophy; Philosophie; Anthropogeografie; Aufsatzsammlung